Women's Legislative Representation and the Pursuit of Gender-Mainstreaming in Public Policy Formulation - Ristina Yudhanti; Moh. Imam Gusthomi; Rizqan Naelufar; Dina Ristanti; Gabriel Aditya Permana S; Deva Sakti Susmana; Halim Rahmansah (Indonesian State Law Review (ISLRev), 2026)
The representation of women in parliament is expected to yield policies that support women's interests. This study examines legal issues related to women's representation in the legislative process, with the aim of formulating policies that prioritize gender mainstreaming for women. The findings indicate that female representation has successfully produced gender-responsive legal instruments that offer protection against the rising incidence of violence against women. The enactment of Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS) constitutes a crucial milestone. Sustained collaboration with relevant stakeholders is essential to ensure the effective implementation of this legislation, including through the formulation of implementing regulations and the enhancement of public awareness. The legislative process undertaken by female legislators in crafting protective policies is inseparable from prevailing cultural challenges. This research constitutes Basic Research employing a socio-legal methodology through qualitative inquiry, utilizing both primary and secondary data sources. The research cluster contributes to assessing the extent to which women's representation in the legislative process advances the formulation of policies that foreground gender mainstreaming. The objective of this study is to measure the degree to which women's representation in the legislative process contributes to the development of policies that prioritize gender mainstreaming for women. This involves an analysis of the messages and narratives conveyed by parliament during the legislative process, and the identification of key factors influencing the effectiveness of women's representation in promoting gender mainstreaming.